Investigation of the mechanical properties of friction-welded joints between AISI 304L and AISI 4340 steel as a function rotational speed - Özdemir, N (Elsevier, 2005)
In this study, standard AISI 304L austenitic stainless steel and AISI 4340 steel couple were welded by friction welding process using five different rotational speeds. The joining performances of AISI 304L/AISI 4340 friction-welded joints were studied and the influences of rotational speed on the microstructure and mechanical properties of the welded joints were also estimated. The microstructural properties of heat affected zone (HAZ) were examined by scanning electron microscopy (SEM). The microhardness across the interface perpendicular to the interface was measured and the strength of the joints was determined with tensile tests. The experimental results indicate that the tensile strength of friction-welded 304L/4340 components were markedly affected by joining rotational speed selected. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: friction welding; microstructure; AISI 304L stainless steel; AISI 4340 steel; rotational speed